(untitled) (Altre Modernità, 2017)
When studying film translation from an historical perspective, it is essential to establish which films were watched by which audience with what kind of consequences (Bosma 2015: 40); to the debate, one should add ‘where’ and ‘when’, as the context obviously must be taken into account. In addition to that, the context – both in terms of space and time – in which the translations of these films have been produced, consumed, and received also plays a key role, not only in determining viewer’s habits and expectations, but also in trying to study from a different and possibly new perspective the traditional subtitling vs. dubbing debate